SOLUSI POLINOMIALPERSAMAAN HERMITE YANG DIPERUMUM - Suriyaamsah '; Asmara Karma; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses how to find a solution of generalized Hermite equation in the form of a polynomial. The discussion focuses on a necessary and sufficient condition for the existence of polynomial solutions of the generalized Hermite equation. By providing certain restrictionson the coefficients of the polynomial, the solution obtained is a monic polynomial.